HUMANITARIAN DIPLOMACY VERSUS DOMESTIC POLITICS : THE DILEMMA OF REFUGEE MANAGEMENT IN INDONESIA - Meganingratna, Andi; Arsyad, Armin; Culla, Adi Suryadi (Universitas Jenderal Ahmad Yani, 2025)
This study examines the complex dilemma faced by Indonesia in managing refugees, particularly the tension between humanitarian diplomacy objectives and domestic political imperatives. Despite not being a signatory to the 1951 Refugee Convention and the 1967 Protocol, Indonesia has become a significant transit country for refugees, with approximately 12,000 displaced persons currently seeking protection within its borders. Employing a qualitative approach and thematic analysis through the theoretical lens of humanitarian diplomacy, this research identifies key political factors influencing refugee management policies in Indonesia. The findings reveal that security concerns, economic considerations, public sentiment, and interest group dynamics significantly shape Indonesia's approach to refugee management. The study demonstrates how Indonesia's humanitarian diplomacy is frequently constrained by competing domestic political discourses and contested protection practices. The research contributes to the literature by analyzing local diplomatic approaches developed by regional governments to navigate these tensions. The study concludes that addressing this dilemma requires systemic transformation through stronger political commitment and a holistic, sustainable approach that harmonizes regulations with international protection standards while acknowledging legitimate domestic concerns. Keywords: refugees, humanitarian diplomacy, domestic politics, national security, refugee management policy, Indonesia